Physical activity domains, levels, and health-related quality of life among Nigerian adolescents during the coronavirus disease 2019 pandemic. (March 2022) - Ugwueze, Fabian Chibunine; Agbaje, Olaoluwa Samson
Introduction: The coronavirus disease 2019 pandemic spurred unprecedented public health measures to curb its spread. Such measures might have negatively impacted adolescents' participation in physical activity and health-related quality of life. However, the evidence is unclear in Nigerian adolescents. This study assessed the physical activity domains, levels, and health-related quality of life in Nigerian adolescents during the coronavirus disease 2019 pandemic. Methods: The sample consisted of 430 students in public secondary schools in Nsukka, Enugu State. The students were randomly selected to participate in the cross-sectional study between November 2020 and April 2021. The Demographic Profile Form, International Physical Activity Questionnaire, Short Form-36 Health Survey, and Perceived Susceptibility to coronavirus disease 2019 Infection Questionnaire were used for data collection. Descriptive statistics, Chi-square test, independent-samples t -test, univariate ANOVA, and multiple linear regressions were conducted using SPSS version 25. Results: The mean score of total physical activity (MET-min/week) was 1651.3 ( SD = 842.18). The mean overall score of health-related quality of life was 78.30 ( SD = 16.43). The mental health component of health-related quality of life showed that adolescents had poor mental health status. Female adolescents had higher mean scores in physical component summary ( M = 83.03; SD = 27.36) and mental component summary ( M = 51.19; SD = 8.69) than the male adolescents, physical component summary ( M = 69.0; SD = 21.65) and mental component summary ( M = 46.15; SD = 10.71). Conclusion: The findings showed a significant positive association among gender, class of study, parental type, perceived susceptibility to coronavirus disease 2019, and physical activity domains, levels, and health-related quality of life. In addition, boys had a higher mean score of total physical activity (MET-min/week) than the girls. More girls were less active than the boys. However, concerning the health-related quality of life, girls had higher mean scores in physical component summary and mental component summary than boys. Physical activity interventions that specifically target female adolescents' physical activity participation are needed. Also, mental health interventions are needed to improve the mental health status of adolescents, especially boys in the post–coronavirus disease 2019 era.